Determinants of selecting the national wrestling team juniors in training centers in the capital, Sana'a - Al-Taweel, Kamal Muhammad; Al-Warafi, Ibrahim Ali (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the most important physical determinants, skill determinants, and special determinants for selecting junior national wrestling team in training centers in Sana'a Capital. (30) junior wrestling players in training centers in Sana'a Capital, and the researcher used the descriptive survey method. The research has reached the following results: building a model for the physical variables for the selection of junior wrestling using factor analysis, which enabled the researcher to reach (4)factors in light of the conditions for accepting the factor, which are as follows. The first factor: (squat test), the second factor: (from standing, bending the torso forward until it touches the ground (. The third factor: (bending the torso from standing backwards), the fourth factor: (from the supine position, the speed of the pressure test exercise), building a model for the skill variables to select the wrestling juniors using factor analysis, enabled the researcher to reach (3) factors in light of the conditions of factor acceptance, which is as follows: The first factor: (the catch of the snatch behind), the second factor: (the catch of the arms and the snatch behind). The third factor: (the catch of the throwing), reaching the building of a model of physical measurements to select the junior wrestling using factor analysis, which enabled the researcher to reaching (5) factors in the light of the conditions for accepting the factor, which are as follows: The first factor: (upper circumference), the second factor: (weight), the third factor: (lower limb length), the fourth factor: (thigh circumference), the fifth factor: (center circumference).
Keywords: Determinants of selecting the national wrestling team juniors; selecting wrestling players; wrestling juniors; wrestling training centers